Alfred North Whitehead : The Man and His Work - Lowe, Victor, 1907-1988 (Book collections on Project MUSE., 1985)
This second volume completes the biography of the influential philosopher, following Whitehead's move first from Trinity College, Cambridge to London, and then, at the age of 63, to America, where the focus of his work shifted from mathematics to philosophy. Lowe (philosophy emeritus, Johns Hopkins U.) died in 1988 with this biography not quite completed. Vol.2 was edited and seen through publication by J.B. Schneewind, chairman of the Philosophy Department at Johns Hopkins. Annotation copyrighted by Book News, Inc., Portland, OR.